2001
DOI: 10.1038/sj.ijo.0801516
|View full text |Cite
|
Sign up to set email alerts
|

Fat balance and serum leptin concentrations in normal, hypothyroid, and hyperthyroid rats

Abstract: OBJECTIVE:To study the in¯uence of thyroid hormones on the relationship between serum leptin and fat mass, as well as on energy and macronutrient balance. DESIGN: Rats with different thyroid states were obtained by 7 and 15 days of treatment with the antithyroid drug propylthiouracil or with triiodothyronine (T 3 ). MEASUREMENTS: Energy balance, macronutrient balance and serum leptin concentrations. RESULTS: In hypothyroid rats we found a decrease in metabolizable energy (ME) intake and energy expenditure toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 27 publications
4
36
0
9
Order By: Relevance
“…Hypothyroid animals had an elevated serum leptin relative to their body weight, which was normalized and even decreased when T3 or T4 were infused. The results were in agreement with 3 other studies (57,59,62) in which hypothyroid rats showed increased leptin mRNA levels and increased leptin secretion, which were acutely reversed by administration of supraphysiological doses of T3 (Table 3).…”
Section: Animal Studiessupporting
confidence: 82%
“…Hypothyroid animals had an elevated serum leptin relative to their body weight, which was normalized and even decreased when T3 or T4 were infused. The results were in agreement with 3 other studies (57,59,62) in which hypothyroid rats showed increased leptin mRNA levels and increased leptin secretion, which were acutely reversed by administration of supraphysiological doses of T3 (Table 3).…”
Section: Animal Studiessupporting
confidence: 82%
“…It has also been reported that insulin secretion is regulated by thyroid hormone (Cortizo et al 1985, Doong et al 1997, and that there is a relationship between serum thyroid hormone levels and diabetes risk (Iossa et al 2001, Crunkhorn & Patti 2008. Hyperthyroidism reduces glucose tolerance in mammals, and the insulin-secretory capacity of the pancreatic islets is reduced by an excess of thyroid hormones (Lenzen & Bailey 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that increased thyroid activity accompanies increased basal metabolism or vice versa: many thyrotoxic patients show increased physical activity and, conversely, many hypothyroid patients complain of lethargy. e mechanisms through which the thyroid hormone is related to the alterations in energy homeostasis and leads to changes in metabolism and molecular pathways have not been clearly identi ed and remain incompletely understood [4,[26][27][28][29]. In this study, we did not detect a di erence in energy expenditure between patients with hypothyroidism and healthy subjects.…”
Section: Resultsmentioning
confidence: 33%